Genetically Engineered Crops: Importance of Diversified Integrated Pest Management for Agricultural Sustainability - Anderson, Jennifer. A.; Ellsworth, Peter C.; Faria, Josias C.; Head, Graham P.; Owen, Micheal D. K.; Pilcher, Clinton D.; Shelton, Anthony M.; Meissle, Michael (Frontiers in Bioengineering and Biotechnology, 2019)
As the global population continues to expand, utilizing an integrated approach to pest management will be critically important for food security, agricultural sustainability, and environmental protection. Genetically engineered (GE) crops that provide protection against insects and diseases, or tolerance to herbicides are important tools that complement a diversified integrated pest management (IPM) plan. However, despite the advantages that GE crops may bring for simplifying the approach and improving efficiency of pest and weed control, there are also challenges for successful implementation and sustainable use. This paper considers how several GE traits, including those that confer protection against insects by expression of proteins from Bacillus thuringiensis (Bt), traits that confer tolerance to herbicides, and RNAi-based traits that confer resistance to viral pathogens, can be key elements of a diversified IPM plan for several different crops in both developed and developing countries. By leveraging the experiences gained with these GE crops, understanding the limitations of the technology, and considering the successes and failures of GE traits in IPM plans for different crops and regions, we can improve the sustainability and versatility of IPM plans for these and future technologies.